The study of alpha particle induced reactions on bismuth-209 isotopes using computer code COMPLET. (7th November 2019) - Asres, Yihunie Hibstie; Mathuthu, Manny; Beyene, Ermias Yitayew
Abstract: Calculations of the excitation function of 209 Bi ( α, n) 212 At, 209 Bi ( α, 2n) 211 At and 209 Bi ( α, 3n) 210 At reactions have been focussed on alpha induced reac t ion. Energy ranges of alpha particles were taken into computations as 10 MeV to 70 MeV. The objective of this study is to compare the computed results with the experimental data existing in the literature for each reactions. The calculated 209 Bi( α, xn) reaction cross-sections were computed using computer code COMPLET and were then compared with the experimental nuclear reaction data obtained from EXFOR library in the literature. This calculated data was analyzed and interpreted with tabular and graphical descriptions. Good agreement was found between the experimental and theoretical data. The results were briefly discussed within the text of this research work.